Penggunaan media simulasi pernafasan untuk meningkatkan kemampuan hasil Belajar ipa siswa sekolah dasar - Muryati, Muryati (Jurnal Pendidikan Dasar, 2022)
The purpose of this paper is to increase the effectiveness of distance learning and students' creative thinking skills in understanding science concepts, especially about the material on the human respiratory system in Class V students at SDN Sabranglor, Surakarta City. Implementation Steps: The preparations made were to make a Learning Implementation Plan (RPP) with an innovative learning design. This learning design is designed by creating distance learning that remains active and creative. Implementation of the Learning Process: The implementation of the learning process is carried out online through the whats app group. Based on the distance learning process that has been implemented, it can be obtained that the use of "Breathing Simulation" media can improve students' creative thinking skills in science learning. This also represents the acquisition of students' scientific literacy. Cognitive, affective, and psychomotor also improve along with the increase in creative thinking skills. the media utilization of "Breathing Simulation" which is carried out online increases student learning motivation. The increase in learning motivation is also in line with the increase in creative thinking skills in elementary school science literacy. Based on the activities that have been carried out and the analysis of the results of the activities, it can be concluded that the use of the "Breathing Simulation" media in science learning is effective in increasing students' creative thinking skills and learning motivation during the Covid-19 pandemic.